Advances in the identification of deciduous molar tooth germs. (February 2021) - Mazzarelli, Debora; Palamenghi, Andrea; Cappella, Annalisa; Zanella, Federica; Breda, Laura; De Angelis, Danilo; Cattaneo, Cristina
Highlights: Information on the identification of loose molar tooth germs are scanty. Gross morphology of the centers is described, and supporting sketches and pictures are provided. Indications for siding the centers are provided. These indications can be used by forensic anthropologists to correctly identify molar tooth germs. Abstract: In forensic anthropology, correct identification of human deciduous teeth is of paramount importance for age-at-death estimation and relies on detailed anatomical descriptions. Yet literature is scarce on indications: details on the morphology of molar tooth germs of fetuses and newborns, developing from multiple mineralized centers that will eventually coalesce, are scant. This paper presents new anatomical elements for practitioners to identify human molar tooth germs at early developmental stages. 126 deciduous molars from 22 modern skeletons of fetuses and newborns (with a known age-at-death ranging between 0 days and 2 months and 21 days postnatal), without reported or observed dental pathological signs, were selected from the Collezione Antropologica LABANOF (CAL) documented skeletal collection. Gross anatomical descriptions of the morphology and configuration of the centers were provided, considering the number of mineralized centers, the shape and the outline of the occlusal plane at different stages. Three different developmental stages were observed in the maxillary first and second molar and the mandibular first molar, whereas in the mandibular second molar four stages were observed. For each stage, we provide additional detailed morphological descriptions, sketches outlining the shape of the tooth germ, and a picture of the tooth; also, indications for siding the teeth are presented. This information can be used by forensic anthropologists and odontologists for a proper identification when tooth germs are not found in anatomical connection within the dental sockets. Further analyses that encompass more age groups on a larger sample would allow to map the entire crown development of deciduous molars.